Evaluation of Fungcoal as a bioprocess technology for self-cladding of waste coal dumps - Sekhohola, Lerato M (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2016)
Low-grade coal, a poor source of energy, has long been regarded as waste material by the coal mining industry. Biological degradation of this coal material by ligninolytic fungal strains presents a viable strategy towards eliminating this unusable fossil fuel. To this end, a novel and patented bioprocess termed Fungcoal was developed. Fungcoal is a biological process utilised in the in situ treatment of waste coal and is based on the mutualistic relationship between the fungus Neosartorya fischeri and the graminaceous species Cynodon dactylon. The process facilitates the rapid conversion of waste coal into soil-like material that stimulates establishment of vegetation for eventual coal dump rehabilitation. While a number of in vitro studies have identified various fungal strains as efficient coal degraders, the mechanisms involved in the Fungcoal-stimulated degradation process have not been fully elucidated. Furthermore, implementation of Fungcoal at both pilot and commercial scale has not been achieved. Thus the objective of this work was to investigate Fungcoal as a bioprocess via examining the role of coal degrading fungi (CDF) and grasses as biocatalysts in coal biodegradation and for the self-cladding of waste coal dumps. Initially, waste coal degradation by N. fischeri, strain ECCN 84, was investigated, specifically focusing on the mechanisms underpinning the process. In vitro studies showed the addition of waste coal induced active fungal colonisation resulting in increased fungal biomass. Increased extracellular laccase (LAC) activity, occuring concomitantly with an increase in hyphal peroxisome proliferation, was also observed in the coal supplied fungal cultures. Analysis of the colonised waste coal revealed a time dependent reduction in the percentage weight of elemental carbon coupled with an increase in elemental oxygen. The results supported metabolism and degradation of waste coal by N. fischeri strain ECCN 84 and involvement of fungal extracellular laccase. The contribution of C. dactylon, a C4 grass species to in situ biodegradation of waste coal in the presence of coal degrading and mycorrhizal fungi (MF) was also investigated. Enhanced degradation of the waste coal into a humic soil-like material was observed within the rhizosphere. Analysis of the resultant substrate revealed an increased concentration of highly oxidised humic-like substances (HS). Fungi remained viable in the rhizosphere up to 47 weeks post-inoculation and cultivation of C. dactylon, indicating the resultant humic substance-rich rhizosphere provided an environment conducive for microbial proliferation and activity. Furthermore, humic substance enrichment of waste coal substrates supported germination and seedling emergence of several agronomic species including Zea mays (corn), Phaseolus vulgaris (bean), Pisum sativum (pea), and Spinacia oleracea (spinach). Use of various cladding materials to support coal biodegradation, by fungus-grass mutualism and rehabilitation of waste dumps was evaluated at commercial scale. While substantial physico-chemical changes were not evident in the absence of cladding or where waste coal was used as cladding material, successful establishment of grass cover and diversity was achieved within three hydrological cycles on dumps cladded with weathered coal. Work presented in this thesis successfully demonstrates the degradation of waste coal by N. fischeri. The biodegradation process included enhanced extracellular LAC activity coupled with increased 3 waste coal oxidation. Increased HS concentration of waste coal substrate supported germination and early seedling establishment of several agronomic species. At commercial scale a co-substrate in the form of carbon-rich weathered coal was essential to support fungus-grass mutualism and Fungcoal-induced rehabilitation. These findings support the developed Fungcoal concept and the underpinning rationale that the phyto-biodegradation of waste coal indeed depends on the mutualistic interactions between grass root exudates and the ligninolytic and mycorrhizal fungi. Taken together, these findings provide practical evidence of the contribution of fungi and grasses as mutualists in the biodegradation of waste coal and sustainable rehabilitation of waste coal dumps
Keywords: Coal mine waste; Fungi -- Biotechnology; Coal -- Biodegradation; Bermuda grass -- Biotechnology